GENETIC VARIABILITY, CORRELATION AND DIVERSITY ANALYSIS OF 12 IMPORTANT JHUM RICE (Oryza sativa. L.) GENOTYPES OF NAGALAND - WANGYAL LEPCHA (The Journal of Research ANGRAU, 2023)
With 12 jhum rice genotypes, the experiment was conducted with a randomized block design and replicated thrice in the year 2022. For every character under the study, the variance estimates between genotypes varied significantly, pointing to a large variation in the samples.Effective tillers/plant followed by 1000-grain weight and grain yield per plant had the highest genotypic coefficient of variation (GCV). Maximum heritability and genetic advance were seen for the 1000-grain weight, the number of grains per panicle and effective tillers/plant. Therefore, using these attributes as selection criteria might result in the accumulation of more additive genes, which will improve their performance, Indicating the relative usefulness of this character for selection,The number of effective tillers per plant, leaf length, leaf width, plant height, panicle length, and 1000- grain weight were significantly correlated positively with grain yield per plant. The study recommended that in order to increase the seed yield, consideration should be given to the number of effective tillers per plant, leaf length, leaf width, plant height, and panicle length. The 12 genotypes of rice were divided into four distinct clusters. Cluster I had two genotypes, Cluster III had two, and Cluster IV had one genotype. Cluster II had six genotypes. Cluster I and cluster IV were found to have the highest inter-cluster divergence, whereas cluster II and cluster III had the lowest divergence. As a result, hybridization programs including genotypes from clusters IV and I can be used.